Strategic human resource management and employment relations an international perspective - Malik, Ashish (Springer texts in business and economics, 2022)
This textbook takes a theoretically informed and practice-based approach to strategic human resource management (HRM) and employment relations (ER). The book follows a unique pedagogical design employing problem-based learning and participant-centred learning approaches, both of which the author has extensive experience in implementing with advanced undergraduate HRM and post-graduate learners. This new edition includes chapters on artificial intelligence (AI) and HR, employee experience and engagement, managing HRM during crises, and eight new cases. In addition, this book includes an online instructors manual for instructors. Ashish Malik is an Associate Professor at the University of Newcastle, Australia and researches and teaches managing human resources strategically. Dr. Maliks research focuses on how HRM can transform and support business model innovation and change for individual performance and sustained competitive advantage. His research has been published in top-tier academic journals, such as the Human Resource Management (US), British Journal of Management, Harvard Business Review, MIT Sloan Management Review, International Journal of HRM, Human Resource Management Review, Journal of Business Research, and Journal of International Management, among others. In addition, Dr Malik has co-edited and authored nine books on HRM and management topics such as business models, human capital formation, high-performance systems and culture in service firms operating in India and overseas.